THE EFFECTS OF DISCIPLINE, MOTIVATION AND LEADERSHIP ON THE WORK QUALITY OF WORKERS AT STATE COLLEGE OF ISLAMIC STUDIES MANDAILING NATAL - sugiharto, Vebri (Eko dan Bisnis: Riau Economic and Business Review, 2020)
ABSTRACT: The aim of this study is to analyze the relation of labor discipline, motivation and leadership on employee performance. The respondents of this research consist of 45 State College Of Islamic Studies (STAIN) Mandailing Natal  employees. The research data based on the result of questionnaire then it is analyzed by multiple linear regression. This equation model is analyzed by SPSS application version 20  for windows. Based on the result of hypotheses, it could be concluded that the labor discipline give positive effect and it is significant on employee performance, Motivation give positive effect and it is significant on employee performance and  leadership give positive effect and it is significant on employee performance,. In the result of this study, leadership is variable that give the big influence on employee performance. The trigger factors of employee performance are working in State College Of Islamic Studies (STAIN) Mandailing Natal  is able to describe and finish the job with the office spirit so that the employee are encouraged  to have a good performances. With the high good leader can push employee work in an optimal fashion in conducting performance, the employee would work optimally and it could improve the results of the performance. Keywords : Labor Discipline, Motivation, Leadership,  Employee Performance